PELAKSANAAN PELAYANAN DASAR BIMBINGAN DAN KONSELING PADA SMA DI KOTA METRO TAHUN AJARAN 2012/2013 - Lilis Puspitaningrum; Syarifuddin Dahlan; ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to describe the implementation of a guidance and counseling at senior high school in Metro City in academic year 2012/2013.The problem of this research is the implementation of guidance and counseling service at senior high school in Metro City was not maximum. The problem was the "extent of the implementation of a guidance and counseling conducted at senior high school in Metro City in academic year 2012/2013?’'. This research used descriptive method. The samples were 40 respondents of senior high school in Metro City. The data collection techniques used questionnaires and interviews about the basic services. The results of this research indicate that guidance and counseling teachers have implemented the basic service components that include the classroom guidance, orientation services, information services, group counseling services, and instrument applications including guidance and counseling in basic services. Overall the implementation of a guidance and counseling at senior high school in Metro City in academic year 2012/2013 reached 77.25%. Based on these results, it could be suggested to : (1) guidance and counseling teachers are expected to be more professional in carrying out further guidance and counseling services and attending many workshops and seminars which related to guidance and counseling so it can increase their insight about the development of guidance and counseling, (2) the school is expected to can establish good cooperation with guidance and counseling teacher in executing the implementation of a guidance and counseling and counseling services in order to realize educational goals and provide the specific time for implementating the guidance and counseling in every class (3) for educational department is expected to not receive the guidance and counseling teachers who the educational background of guidance and counseling, (4) the further researcher is expected to conduct the further research which relate about the implementation of guidance and counseling at senior high school in order to support and to fix the result of this research.Keywords: basic services, guidance and counseling, senior high school